Industrial control and instrumentation - Bolton, W. (Longman Scientific & Technical, 1991)
This text provides a comprehensive introduction to the principles of industrial control and instrumentation. The author not only outlines the basic concepts and terminology of measurement and control systems, he also discusses in detail the elements used to build up such systems. As well as a final consideration of measurement and control systems, each chapter concludes with relevant problems in order that students can test their newly acquired knowledge as they progress. Students studying for BTEC National Certificate and Diploma courses in electrical and electronic, communications and computer engineering will find that their course requirements are more than satisfied by this comprehensive text.